LPV systems analysis using pseudospectra - Alamin, Raheeg; Whidborne, James F.; Alam, Mushfiqul (IEEE, 2022)
Pseudospectra provides a qualitative and quantitative tool for analyzing the stability sensitivity of linear systems. In this paper pseudospectral analysis is extended to Linear Parameter Varying (LPV) systems that are approximated by frozen sets. Two examples of quasi-LPV system models are analyzed, namely an actuated pendulum system and a 2-DOF aeroelastic flutter model. It is shown that use of pseudospectra can overcome some limitations of classical eigenvalue sensitivity as well as providing qualitative information that is straightforward to interpret. Some limitations are discussed and suggestions for further work included.
Keywords: Perturbation; Eigenvalue sensitivity; Pseudospectra; Aeroelasticity; LPV